Quality-of-Life Community Indicators for Parks, Recreation and Tourism Management
XVIII, 230 p.
Keywords: Within the parks and recreation field, measuring the effectiveness of recreation programs or resource management is vitally important. The same holds true for tourism management. Community indicators represent a way to assess management frameworks and gauge their impact on quality of life. The three areas of parks, recreation and tourism comprise an integrated academic discipline. Across the globe, researchers in this discipline are conducting innovative indicator research; however, very little literature is available. This books rises to fill that need by providing a compendium of example studies that reflect the range of work currently being conducted. Quality-of-Life Community Indicators for Parks, Recreation and Tourism Management presents cutting-edge research in community indicators, focusing on quality-of-life aspects. It covers many topics, such as indicators and its standards in parks and outdoor recreation, leisure and relationship to quality-of-life satisfaction, development of a tourism and quality-of-life instrument, and sustainability indicators for managing community-based tourism as well as other sustainability issues. In addition, it details models of successful indicator systems and includes case studies from around the world. Aimed at students and researchers interested in the application of community indicator systems to pertinent issues in parks, recreation and tourism, this book simultaneously informs on the latest research in the area while providing impetus for future research efforts.